“It’s a Choice”: Graduate Student Mothers’ Sense of Agency in Decision-Making - Paré, Elizabeth R. (Journal of the Motherhood Initiative for Research and Community Involvement, 2016)
Although a growing number of research universities have formal student-parentpolicies, many do not. Graduate student mothers attending institutions withoutstudent-parent policies must make decisions and exercise agency within this context.This work explores the sense of agency and decision making of ten graduate studentmothers raising young children (under the age of five) while attending a researchuniversity without official student-parent policies. The findings demonstrate thatwomen attempt to exercise their sense of agency by separating motherhood fromschool and by negotiating individual solutions to conflicts. Findings also indicatethat the choices and agency exercised provide power in a temporary capacity butdo not provide long-term power or control over schooling and family life. Overall,this research highlights the importance of formal policies and support for studentmothers; without these policies, women’s agency and their ability to participate fullyin graduate school are limited.